Os (entre) lugares da Arte na Educação Infantil (Revista Apotheke, 2019)
This article proposes a moment of reflection on Art Teaching in Early Childhood Education. From the ideal to the possible there is an extensive course of doings and challenges. We give a brief overview of how the field of art knowledge is understood in early childhood education and to counterpoint some pedagogical practices where we approach the artistic languages. Proposing to think about how art is placed in this intertwining of knowledge construction in this teaching time, the theoretical framework is based on authors who made it possible to base our speech in order to highlight art as a field of knowledge that contributes to pedagogical practices.
Keywords: arte; educación infantil; prática docente